The Effect of Using “SMARICALITION” Poster on Students’ Writng Skill at SMA N 2 Tanjung Pinang - Rona Elfiza; Ratna (J-SHMIC : Journal of English for Academic, 2020)
Writing an analytical exposition text is one of the skills that should be mastered by students in Senior High School. Teaching medium has an important role to facilitate the students in writing analytical exposition text. SMARICALITION (Smart Analytical Exposition) Poster is one of the media can be used in teaching writing analytical exposition text. This article retrieved from the research on the effect of using SMARICALITION Poster on students’ writing skill of SMAN 2 Tanjungpinang. This research was conducted as quasi-experimental research. The purpose of the study is to test whether SMARICALITION Poster gives a significant effect on students’writing skill or not. The population of this research was the 11th-grade students of SMAN 2 Tanjungpinang. There were five classes of social major and seven classes of science major. The sample of this study was XI Science 3 and XI science 4. XI Science 3 was the experimental group, whereas XI Science 4 was the control group. There were 38 students investigated in each class. The sample was taken by using multistage cluster sampling. This study used a written test as its instrument. The result of this research was students’ writing skill who were taught by using SMARICALITION Poster was better than students’ speaking skill who weren’t taught by SMARICALITION Poster. It can be concluded that SMARICALITION Poster gave significant effect on students’ writing skill at SMAN 2 Tanjungpinang.